2011
DOI: 10.1007/s00231-011-0944-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tip gap and amplitude of piezoelectric fans on the performance of heat sinks in microelectronic cooling

Abstract: Piezoelectric fan is a promising option for cooling microelectronic devices owing to its unique features such as no electromagnetic noise, low power consumption and minimum space requirement. The recent interest is to integrate the piezoelectric fans (piezofans) with heat sink; this idea is widely accepted and researches are still underway. This article presents experimental analysis on the effects of tip gap (d) and amplitude of piezofan vibration (a) on the heat transfer characteristics of finned heat sinks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To combine the effect of the Mylar plate width and the vibrating amplitude, the characteristic length (L PZT ) is defined as the hydraulic diameter, as described in Eq. (8).…”
Section: Thermal Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…To combine the effect of the Mylar plate width and the vibrating amplitude, the characteristic length (L PZT ) is defined as the hydraulic diameter, as described in Eq. (8).…”
Section: Thermal Analysismentioning
confidence: 95%
“…Abdullah et al [8] investigated the thermal characteristics of the heat sink with three piezofans, and the results showed that the fan's effectiveness was increased to almost 4 times than the case without piezofans. Sufian et al [9] investigated the thermal performance of two piezoelectric fans in multi-LED packages.…”
Section: Introductionmentioning
confidence: 97%
“…This is in contrast to much of the literature on oscillating piezoelectric fans where airflow emanates in a forward direction from the fan tip. The cooling capabilities of these airflows as they impinge on a heated surface have been studied extensively ( [5], [11], [12], [13]). The lateral wake regions in the current work Fig.…”
Section: X-y Plane Measurementsmentioning
confidence: 99%
“…The most recent studies focus on the thermal performance of plate-fin heat sinks and the optimization of the position of the piezo fan based on the peak-to-peak displacement amplitude, proximity to the heat source, orientation of the fan and/or number of fins of the heat sink needed to obtain the maximum performance out of the piezoelectric fan arrays. Such investigations can be observed in the work from Abdullah et al [13] and Li et al [14] Most of these investigations have been done using piezoelectric fans with a resonance frequency not larger than 120Hz with a fan length between 4 and 8cm and a footprint area on the order of 6-9cm 2 and a peak-to-peak displacement amplitudes of approximately 10-20mm and without any additional air flow source.…”
Section: Introductionmentioning
confidence: 95%